Interactive Surgical Liver Phantom for Cholecystectomy Training - Schüßler, Alexander; Younis, Rayan; Paik, Jamie; Wagner, Martin; Mathis-Ullrich, Franziska; Kunz, Christian-Peter (Current Directions in Biomedical Engineering, 2024)
Training and prototype development in robotassisted surgery requires appropriate and safe environments for the execution of surgical procedures. Current dry lab laparoscopy phantoms often lack the ability to mimic complex, interactive surgical tasks. This work presents an interactive surgical phantom for the cholecystectomy. The phantom enables the removal of the gallbladder during cholecystectomy by allowing manipulations and cutting interactions with the synthetic tissue. The force-displacement behavior of the gallbladder is modelled based on retraction demonstrations. The force model is compared to the force model of ex-vivo porcine gallbladders and evaluated on its ability to estimate retraction forces.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Cholecystectomy; Force Modeling; Robotassisted Surgery; Surgical Phantom; Surgical Training

Statistical Shape Models for Grasp Point Determination in Laparoscopic Surgeries - Kunz, Christian-Peter; Kraus, Maria; Younis, Rayan; Wagner, Martin; Mathis-Ullrich, Franziska (Current Directions in Biomedical Engineering, 2024)
Robotic assistance systems are being used more and more frequently in the operating room, with the goal to support surgeons and to automate parts of a procedure. The laparoscopic cholecystectomy is one of the most common procedures in Germany.We aim to automate the assistant grasp task in this procedure. To achieve this goal, first the grasp points on the gallbladder need to be determined. In this work, we therefore present a statistical shape model fitting to the gallbladder for grasp point determination. Gallbladder and liver point clouds are utilized as inputs. A registration algorithm is used to fit the shape model to the gallbladder mesh. The process is evaluated on three different datasets achieving a successful grasping point identification of 90% for artificially created gallbladders, 100% for our silicon phantom model, and 90% for ex-vivo organs.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Cholecystectomy; Grasp Point Determination; Robot-assisted Surgery; Statistical Shape Models